Case Report: Effect of Electroconvulsive Therapy on Obsessive-Compulsive Disorder Comorbid With Body Dysmorphic Disorder - Ma, Xiaoyan; Li, Ranli (Frontiers in Psychiatry, 2021)
Abstract: Obsessive-compulsive disorder (OCD) is a chronic psychiatric condition that is associated with considerable morbidity, and approximately 90% of individuals with OCD have another psychiatric comorbidity. Patients with comorbid OCD and body dysmorphic disorder (BDD) have limited insight and poor psychosocial function, respond poorly to drug treatment, and have an increased risk of suicide. Modified electroconvulsive therapy (ECT) has been attempted to improve symptoms of OCD when drug treatment does not have a satisfactory effect. This report describes a patient who had OCD comorbid with BDD that was successfully treated with modified ECT. Although the mechanism of its effect is unclear, modified ECT may be an alternative treatment for patients with comorbid OCD and BDD. Its efficacy and mechanism of action require further investigation in a large sample of patients with these comorbid disorders.